Cost-benefit analyses and business designs for inclusive models proposed by companies selected to work in agroecology-initiative areas in Zimbabwe - Dawes, Michael; Mushongachiware, Rodney (CGIAR, 2023)
This report presents the business plan designs and cost-benefit analyses for selected companies cooperating with the ‘transformational agroecology across food, land, and water systems’ programme, also known as the Agroecological Initiative (AE-I).In Mbire district, the sorghum value chain was prioritised because of the enthusiasm of the contracting company and positive results from the cost benefit analyses showing profitability for both the company and contracted farmers. With modest AE-I support, the company is predicted to show a small profit by the twelfth month, paving the way for expansion of the contract farming programme in 2024. The company is also supporting the village business threshing model, proposed during 2022 as a standalone model as there are good synergies. In the same district, delays have been experienced with a livestock abattoir project that showed excellent qualitative analysis results. In Murehwa district a Sasso chicken project showed good returns to both farmers and the implementing company. The company is supporting the previously proposed village business brooding model which will increase its sales and support economic diversification in the district. Implementation modalities for both projects were firmly underway by mid-October 2023.